Seagrass morphological traits in Changuu Island (Zanzibar Archipelago, Tanzania) during a macrofauna exclusion and nutrient enrichment experiment - Agustín Moreira-Saporiti; Mirta Teichberg; Aoife O extquotesingleSullivan (PANGAEA, 2026)
Seagrass morphological traits (leaf maximum length, leaf maximum width, sheath length and rhizome diameter) were measured during a nutrient enrichment and macrofauna exclusion experiment. A total of 24 plots were set up parallel to the shore, with presence of the three seagrass species (Syringodium isoetifolium, Thalassodendron ciliatum and Thalassia hemprichii) in each plot. The experiment was the factorial combination of two treatments: macrofauna exclusion using cages (three levels: open, closed and uncaged) and nutrient enrichment using garden NPK fertilizer (two levels: ambient and enriched). Each treatment combination was replicated four times. Exclusion treatment simulates the consequences for the food web of losing a top predators and macrograzers. Nutrient enrichment was simulated by issuing nitrogen-phosphorus-potassium (NPK) [15:9:20] fertilizer pellets. NPK fertilizer fast release pellets were packed into cotton tubes and then into a perforated plastic tubes to simulate slow release of nutrients. The tubes were buried half-way into the sediment to ensure enrichment of both the water column and the sediment. Data was collected between July 19th and September 20th of 2017 in four sampling times. Day 0 (19.07.2017), Day 20 (09.08.2017), Day 38 (31.08.2017) and Day 63 (19.09.2017). Data collection and experiment took place in Changuu Island (Zanzibar Archipelago, Tanzania; 0611 extquotesingleS, 3916 extquotesingleE). Changu Island is located 3 km from Stone Town, Zanzibar extquotesingles busiest town. Changuu remains relatively unaffected by nutrient runoff pollution. The study area is characterised by a fringing reef around a multi-specific seagrass ecosystem. The substrate is primarily carbonate sediment. Average water depth is approximately 30 cm at Spring Low and 5 m at Spring high tide with an average depth of 2 m. Seagrass morphological traits were measured to understand the morphological responses of the three seagrass species present in Changuu Island to the nutrient enrichment and macrofauna exclusion treatments. To determine the morphological responses of the seagrass species to the treatments, we measured traits linked to disturbance, and specifically nutrient enrichment and eutrophication. Three ramets of each species were collected per treatment plot and sampling time from the biomass cores used to determine seagrass biomass. One biomass core was taken per experimental plot, with a radius of 15cm. The morphological traits were measured once for each ramet collected. In the case of the traits measured at the shoot level, the biggest shoot was always selected to avoid the confounding effect of young and newly sprouted shoots. The traits measured were: Maximum leaf length (Leaf ML, cm), maximum leaf width (Leaf MW, cm; for S. isoetifolium, the maximum diameter of the leaf was measured), sheath length (SheathL, cm), and number of leaves per shoot (Leaves/Sh, leaves shoot -1) as indicators for changes in the aboveground structures. Rhizome diameter (RhD, cm) was measured as an indicator for changes in the belowground structures. The three values measured were then averaged per experimental plot. All the traits in length units were measured with a ruler to the nearest millimeter.